Reform of Environmental Approval Policy for Renewable Energy in Indonesia - Ketut Rachmi Handayani , I Gusti Ayu; Yosiana, Cindy; Kongrawd , Sutasinee (Lembaga Contrarius Indonesia, 2025)
Indonesia faces persistent regulatory barriers in accelerating its renewable energy transition, mainly due to rigid and bureaucratic environmental licensing that ignores the specific characteristics of clean energy projects. This study examines the legal and policy gaps in Indonesia’s environmental licensing framework, using a normative legal approach complemented by case studies and comparative analysis with Germany, Australia, and selected ASEAN countries. The findings reveal three main issues. First, although Indonesia has adopted a risk-based licensing system through the OSS RBA, the country still applies uniform procedures to all projects, failing to distinguish between high- and low-risk activities. It discourages investment and slows the growth of small-scale renewable energy. Second, the principles of prudence and sustainability have not been effectively reflected in policy implementation. There is an urgent need for reforms that align licensing procedures with project risks, strengthen public participation, ensure protection for vulnerable groups, and leverage digital technologies for greater transparency. Third, international comparisons show that countries such as Germany, Australia, Vietnam, Thailand, and Laos have successfully accelerated clean energy adoption by implementing risk-based regulations, simplifying procedures, offering financial incentives, and improving intergovernmental coordination. Based on these insights, the study recommends that Indonesia reform its environmental licensing policies to be more adaptive, transparent, and proportionate to project risks, thus supporting legal certainty, ecological justice, and a sustainable energy transition.